Multi-robot Approach for Automation of an Industrial Profile Lamination Process - Bielawny, Dirk; Bruns, Torsten; Loh, Chia Choon; Trächtler, Ansgar (2012 International Symposium on Robotics and Intelligent Sensors (IRIS))

A self-correcting Approach for the Bending of Metal Parts - Damerow, Ulf-Hendrik; Borsig, Michael; Homberg, Werner; Trächtler, Ansgar (Key Engineering Materials Vols. 504-506 (2012))

Cascaded Heterogeneous Simulations for Analysis of Mechatronic Systems in Large Scale Transportation Scenarios - Hassan, Bassem; Wassmann, Helene; Klaas, Alexander; Kessler, Jan Henning (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference)

Model-based Design of Self-Correcting Strategy for a Punch Bending Machine - Borsig, Michael; Trächtler, Ansgar; Damerow, Ulf-Hendrik; Homberg, Werner (14th IFAC Symposium on Information Control Problems in Manufacturing, INCOM 2012)

Human in the Loop: Optimal Control of Driving Simulators and New Motion Quality Criterion - Al Qaisi, Imad; Trächtler, Ansgar (IEEE International Conference on Systems, Man and Cybernetics - IEEE SMC 2012)

Analyzing Product Lifecycle Costs for a Better Understanding of Cost Drivers in Additve Manufacturing - Lindemann, C.; Jahnke, U.; Moi, M.; Koch, R. (23rd Annual International Solid Freeform Fabrication Symposium)
The costs of additive manufactured parts often seem too high in comparison to those of traditionally manufactured parts, as the information about major cost drivers, especially for additive manufactured metal parts, is weak. Therefore, a lifecycle analysis of additive manufactured parts is needed to understand and rate the cost drivers that act as the largest contributors to unit costs, and to provide a focus for future cost reduction activities for the Additive Manufacturing (AM) technology. A better understanding of the cost structure will help to compare the AM costs with the opportunity costs of the classical manufacturing technologies and will make it easier to justify the use of AM manufactured parts. This paper will present work in progress and methodology based on a sample investigated with business process analysis / simulation and activity based costing. In addition, cost drivers associated with metal AM process will be rated.

Long-Term ageing effects on Fused Deposition Modeling Parts manufactured with ULTEM*9085 - Bagsik, A.; Schöppner, Volker; Klemp, E. (23rd Annual International Solid Freeform Fabrication Symposium)
Relating to the direct manufacturing of end-use parts the knowledge about the effect of the long-term ageing of Fused Deposition Modeling (FDM) parts is of particular importance. For this, tensile specimens were stored for time periods of up to 52 weeks in two different conditions and the testing was conducted at different temperatures within a temperature range of -60°C to +160°C. Further tests were made after the exposure in multiple media. The parts were built up with the system “Fortus 400mc” from Stratasys with the material Ultem*9085 in two different build directions, the strongest direction X (on its side) and the weakest build direction Z (upright) and with the standard toolpath parameters of the Insight software version 7.0.

Average and competitive analysis of latency and power consumption of a queuing system with a sleep mode - Herlich, Matthias; Karl, Holger (Proceedings of the 3rd International Conference on Energy-Efficient Computing and Networking, e-Energy'12, Madrid, Spain, May 9-11, 2012)

Cooperating base station set selection and network reconfiguration in limited backhaul networks - Dräxler, Martin; Biermann, Thorsten; Karl, Holger; Kellerer, Wolfgang (23rd IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2012, Sydney, Australia, September 9-12, 2012)

Towards an Automatic Service Discovery for UML-based Rich Service Descriptions - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the ACM/IEEE 15th International Conference on Model Driven Engineering Languages and Systems (MoDELS))
Service-oriented computing (SOC) promises to solve many issues in the area of distributed software development, e.g. the realization of the loose coupling pattern in practice through service discovery and invocation. For this purpose, service descriptions must comprise structural as well as behavioral information of the services otherwise an accurate service discovery is not possible. We addressed this issue in our previous paper and proposed a UML-based rich service description language (RSDL) providing comprehensive notations to specify service requests and offers.However, the automatic matching of service requests and offers specified in a RSDL for the purpose of service discovery is a complex task, due to multifaceted heterogeneity of the service partners. This heterogeneity includes the use of different underlying ontologies or different levels of granularity in the specification itself resulting in complex mappings between service requests and offers. In this paper, we present an automatic matching mechanism for service requests and offers specified in a RSDL that overcomes the underlying heterogeneity of the service partners.

Towards a Framework for the Integration of Modeling Languages - Arifulina, Svetlana (Proceedings of the Doctoral Symposium of the 5th International Conference on Software Language Engineering 2012, Dresden, Germany (SLE (Doctoral Symposium)))
In software markets of the future, customer-specific software will be developed on demand from distributed software and hardware services available on world-wide markets. Having a request, services have to be automatically discovered and composed. For that purpose, services have to be matched based on their specifications. For the accurate matching, services have to be described comprehensively that requires the integration of different domain-specific languages (DSLs) used for functional, non-functional, and infrastructural properties. Since different service providers use plenty of language dialects to model the same service property, their integration is needed for the matching. In this paper, we propose a framework for integration of DSLs. It is based on a parameterized abstract core language that integrates key concepts needed to describe a service. Parts of the core language can be substituted with concrete DSLs. Thus, the framework serves as a basis for the comprehensive specification and automatic matching of services.

Evaluation of Technical Communication - Menke, Peter (Handbook of Technical Communication)

Coverage Criteria for Testing DMM Specifications - Arifulina, Svetlana; Engels, Gregor; Soltenborn, Christian (Proceedings of the 11th International Workshop on Graph Transformation and Visual Modeling Techniques (GT-VMT))
Behavioral modeling languages are most useful if their behavior is specified formally such that it can e.g. be analyzed and executed automatically. Obviously, the quality of such behavior specifications is crucial. The rule-based semantics specification technique Dynamic Meta Modeling (DMM) honors this by using the approach of Test-driven Semantics Specification (TDSS), which makes sure that the specification at hand at least describes the correct behavior for a suite of test models. However, in its current state TDSS does not provide any means to measure the quality of such a test suite. In this paper, we describe how we have applied the idea of test coverage to TDSS. Similar to common approaches of defining test coverage criteria, we describe a data structure called invocation graph containing possible orders of applications ofDMM rules. Then we define different coverage criteria based on that data structure, taking the rule applications caused by the test suite’s models into account. Our implementation of the described approach gives the language engineer using DMM a means to reason about the quality of the language’s test suite, and also provides hints on how to improve that quality by adding dedicated test models to the test suite.

Archimetrix: Improved Software Architecture Recovery in the Presence of Design Deficiencies - Platenius, Marie Christin; von Detten, Markus; Becker, Steffen (Proceedings of the 16th European Conference on Software Maintenance and Reengineering (CSMR))
Maintaining software systems requires up-to-date models of these systems to systematically plan, analyse and execute the necessary reengineering steps. Often, no or only outdated models of such systems exist. Thus, a reverse engineering step is needed that recovers the system’s components, subsystems and connectors. However, reverse engineering methods are severely impacted by design deficiencies in the system’s code base, e.g., they lead to wrong component structures. Several approaches exist today for the reverse engineering of component-based systems, however, none of them explicitly integrates a systematic design deficiency removal into the process to improve the quality of the reverse engineered architecture. Therefore, in our Archimetrix approach, we propose to regard the most relevant deficiencies with respect to the reverse engineered component-based architecture and support reengineers by presenting the architectural consequences of removing a given deficiency. We validate our approach on the Common Component Modeling Example and show that we are able to identify relevant deficiencies and that their removal leads to an improved reengineered architecture.

Archimetrix: A Tool for Deficiency-Aware Software Architecture Reconstruction - von Detten, Markus (Proceedings of the 19th Working Conference on Reverse Engineering (WCRE))
Maintaining software systems requires up-to-date models of these systems to systematically plan, analyze, and execute the necessary reengineering steps. Often, no or only outdated models of such systems exist.Thus, a reverse engineering step is needed that recovers the system's components, subsystems, and connectors. However, reverse engineering methods are severely impacted by design deficiencies in the system's code base, e.g., they lead to wrong component structures.Therefore, Archimetrix enables the reengineer to detect the most relevant deficiencies with respect to a reverseengineered component-based architecture and supports him by presenting the architectural consequences of removinga given deficiency.

A UML-based Rich Service Description for Automatic Service Discovery - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the Forum at the CAiSE'12 Conference on Advanced Information Systems Engineering)
Service-oriented computing (SOC) emerges as a promising trend solving many issues in distributed software development. Following the essence of SOC, service descriptions are dened by the service partners based on current standards, e.g., WSDL [15]. However, these standards are mostly structural and do not provide any behavioral description, which may lead to inaccurate service discovery results. There is a requirement for a rich service description language for service partners that encompasses the structural as well as behavioral information in the service description. Furthermore, service discovery based on an automatic matching of these comprehensive service descriptions is a complex task, which is further complicated through the heterogeneity of the service partners' domains in terms of dierent underlying ontologies. In this paper, we propose a rich service description language based on UML, which allows the specication of structural and behavioral features of a service. In addition, we also briefly discuss how some existing matching approaches can be extended to dene an automatic matching mechanism for rich service descriptions resolving the underlying heterogeneity.

Studienprogramme als hochschuldidaktische Gestaltungs-und Untersuchungseinheit - Jenert, Tobias
In den vergangenen Jahren wurden viele Vermutungen über die "Wirkungen" von Bologna auf das Studieren geäussert: Schlagworte wie Verschulung oder Entwissenschaftlichung sind zu hören und Studierende stehen im Verdacht, ihr Studium eher als Credit-Point-Jagd denn interessengeleitet zu gestalten (z.B. Stegemann, 2007, o. S.; Schultheis, et al. 2008). Meist handelt es sich jedoch um anekdotischen Beschreibungen, bis auf wenige Ausnahmen fehlen empirisch belegte Erkenntnisse.1 Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig darüber bekannt, wie sie den langfristigen Bildungsprozess eines ganzen Studiums gestalten. Vorwiegend wurde Lernen im engeren Sinne, das so genannte "Classroom Learning" untersucht (Aineley, 2008). Forschungsfokus. Die diesem Beitrag zugrunde liegende Studie nimmt diese Forschungslücke auf und untersucht Zielvorstellungen und Handlungsstrategien Studierender bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen. Im Einzelnen wird gefragt, (1) welche Vorstellungen und Wahrnehmungen das Handeln Studierender prägen und (2) welche programmspezifischen Kontextbedingungen die Herausbildung dieser handlungsleitenden Charakteristika beeinflussen. Als theoretischer Rahmen wurde die so genannte Kulturpsychologie herangezogen, die Handeln als Resultat einer Wechselwirkung von individuell-psychischen Merk-malen und sozio-kulturell vermittelten Vorstellungen versteht (Shweder, 1991; Bruner, 1990).
Keywords: Hochschulentwicklung; Studienprogramme; Curriculum Development; Higher Education; Faculty Development

Studierende (als) Kunden?: Zum Umgang mit einer herausfordernden Beziehung zwischen Lehrenden und Lernenden - Jenert, Tobias; Fust, Alexander (Lernendenorientierung: Studierende im Fokus)

Frequency tuning of piezoelectric energy harvesters by magnetic force - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Smart Materials and Structures)
A piezoelectric energy harvester is an electromechanical device that converts ambient mechanical vibration into electric power. Most existing vibration energy harvesting devices operate effectively at a single frequency only, dictated by the design of the device. This frequency must match the frequency of the host structure vibration. However, real world structural vibrations rarely have a specific constant frequency. Therefore, piezoelectric harvesters that generate usable power across a range of exciting frequencies are required to make this technology commercially viable. Currently known harvester tuning techniques have many limitations, in particular they miss the ability to work during harvester operation and most often cannot perform a precise tuning. This paper describes the design and testing of a vibration energy harvester with tunable resonance frequency, wherein the tuning is accomplished by changing the attraction force between two permanent magnets by adjusting the distance between the magnets. This tuning technique allows the natural frequency to be manipulated before and during operation of the harvester. Furthermore the paper presents a physical description of the frequency tuning effect. The experimental results achieved with a piezoelectric bimorph fit the calculated results very well. The calculation and experimental results show that using this tuning technique the natural frequency of the harvester can be varied efficiently within a wide range: in the test setup, the natural frequency of the piezoelectric bimorph could be increased by more than 70%.

Analytical determination of characteristic frequencies and equivalent circuit parameters of a piezoelectric bimorph - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
Piezoelectric structures are nowadays used in many different applications. A better understanding of the influence of material properties and geometrical design on the performance of these structures helps to develop piezoelectric structures specifically designed for their application. Different equivalent circuits have been introduced in the literature to investigate the behaviour of piezoelectric transducers. The model parameters are usually determined from measurements covering the characteristic frequencies of the piezoelectric transducer. This article introduces an analytical technique for calculating the mechanical and electrical equivalent system parameters and characteristic frequencies based on material properties and geometry for a cantilever bimorph structure. The model is validated by measurements using a cantilever bimorph and fits the experimental results better than previous models. The model gives a full set of piezoelectric transducer parameters and is therefore well suited for further theoretical investigations of piezoelectric transducers for different applications. The results also show that even small manufacturing tolerances have a considerable effect on the system parameters and characteristic frequencies. This might lead to intolerable deviations, especially in dynamic applications and should be avoided by careful design and production.